Procedural Outcomes and Survival After Catheter Ablation of Ventricular Tachycardia in Relation to Electroanatomical Substrate in Patients With Nonischemic‐Dilated Cardiomyopathy: The Role of Unipolar Voltage Mapping. (28th July 2015) - DINOV, BORISLAV; SCHRATTER, ALEXANDRA; SCHIRRIPA, VALENTINA; FIEDLER, LUKAS; BOLLMANN, ANDREAS; ROLF, SASCHA; SOMMER, PHILIPP; HINDRICKS, GERHARD; ARYA, ARASH
Scar and Outcomes Of VT Ablation in Nonischemic DCM Introduction In patients with ischemic cardiomyopathy the size of bipolar low‐voltage areas (LVA) in electroanatomical maps (EAM) was associated with poorer outcomes after catheter ablation (CA) of ventricular tachycardia (VT). However, the effect of LVA size on the survival after VT ablation in patients with nonischemic dilated cardiomyopathy (NIDCM) has not been studied. Methods and Results In 55 patients with NIDCM (48 male, age 61 ± 16 years, ejection fraction 32 ± 13%) an EAM to delineate the bipolar and unipolar LVAs was performed in 52 (94.5%) patients endocardially, in 24 (43.6%) patients epicardially, and in 21 (38.2%) patients on both surfaces. Additionally, activation mapping of the VT was possible in 22 (40%) patients. CA with lines transecting the scar and targeting late potentials was performed in all patients. Complete VT noninducibility at the end was achieved in 40 (72.7%) patients. During the median follow‐up of 22 (interquartile range IQR 6, 34) months, VT recurrences were observed in 30 (54.5%) and cardiac death in 14 (25.5%) patients. The ROC analysis revealed that the size of endocardial unipolar LVA (<8.3 mV) was associated with cardiac death (AUC 0.89, 95% CI 0.79–0.98, P <0.0001). UVA = 145 cm2 discriminates for cardiac death with 83% sensitivity and 78% specificity. Endocardial UVA > 145 cm2 was a predictor for cardiac death (adjusted HR = 6.9; P = 0.014) and UVA ≥ 54% (of total endocardial LV surface) for VT recurrence (adjusted HR = 3.5; P = 0.016). Conclusion The size of endocardial unipolar LVA (<8.3 mV) was a strong and independent predictor for cardiac mortality and VT recurrence in patients with NIDCM.